Brachygnathia, cardiomegaly and renal hypoplasia syndrome (BCRHS) in Merino sheep maps to a 1.1‐megabase region on ovine chromosome OAR2. (4th July 2012) - Shariflou, M. R.; Wade, C. M.; Kijas, J.; McCulloch, R.; Windsor, P. A.; Tammen, I.; Nicholas, F. W.
Summary A genome scan was conducted to map the autosomal recessive lethal disorder brachygnathia, cardiomegaly and renal hypoplasia syndrome (BCRHS) in Poll Merino sheep. The scan involved 10 affected and 27 unaffected animals from a single Poll Merino/Merino sheep flock, which were genotyped with the Illumina Ovine SNP50 BeadChip. Association and homozygosity mapping analyses located the disorder in a region comprising 20 consecutive SNPs spanning 1.1 Mb towards the distal end of chromosome OAR2. All affected animals and none of the unaffected animals were homozygous for the associated haplotype in this region. These results provide the basis for identifying the causative mutation(s) and should enable the development of a DNA test to identify carriers in the Poll Merino sheep population. Understanding the molecular control of BCRHS may provide insight into the fundamental genetic control and regulation of the affected organ systems.